2019
DOI: 10.1103/physrevapplied.12.034019
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Ghost Imaging

Abstract: We study the reconstruction algorithm effect on the positive and negative ghost imaging (GI). By introducing three GI algorithms (logarithmic GI, exponential GI and trigonometric GI), we perform numerical simulations and experiments with different GI algorithms, which demonstrate that a positive or negative ghost image can be recovered by modulating the monotonicity of the bucket object signal function. Furthermore, we propose a positive-negative optical encryption scheme based on trigonometric GI. Our work no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In DGI algorithm, the bucket object signal function is defined as 27 where is the total intensity of the reference beam in the i th measurement. In NGI algorithm, the bucket object signal function is defined as 28 In analogy to the definitions of DGI and NGI, we recently proposed the LGI and EGI algorithms by defining the bucket object signal as logarithmic and exponential functions of , respectively 30 . Thus, the reconstruction algorithm of LGI is where A is the base of the logarithmic function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In DGI algorithm, the bucket object signal function is defined as 27 where is the total intensity of the reference beam in the i th measurement. In NGI algorithm, the bucket object signal function is defined as 28 In analogy to the definitions of DGI and NGI, we recently proposed the LGI and EGI algorithms by defining the bucket object signal as logarithmic and exponential functions of , respectively 30 . Thus, the reconstruction algorithm of LGI is where A is the base of the logarithmic function.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we compare imaging reconstruction efficiency and error tolerance of six representative GI algorithms, together with logarithmic GI and exponential GI we proposed 30 . Numerical simulations show that compressive GI algorithm takes a great advantage in the imaging reconstruction process due to its global optimization property.…”
Section: Introductionmentioning
confidence: 99%
“…We use the Fourier matrix to generate sinusoidal and cosine structural illumination patterns, both of which can reconstruct images in the imaging course with symmetrical overlapping shadows due to missing phase information. A clear image is finally reconstructed by applying the intensity correlation to the negative and positive images for phase compensation [13,14,33,34],…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Researchers have shown that an image can be captured with just one pixel based on spatially structured illumination and multiple measurements in the time domain. This technique is called computational single-pixel imaging (SPI), also known as ghost imaging (GI) [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first demonstrations of correlated imaging and interference with entangled sources 1,2 , correlation has been a hot topic in the area of quantum imaging. To achieve a high qualified image, a lot of schemes were explored [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Besides imaging, interference was widely discussed with correlation method [20][21][22][23][24][25] .…”
mentioning
confidence: 99%